Simplify by using the Distributive Property and combining of similar terms: 5(x + 3) - 4(2x - 1)
- 3x + 11
- 13x + 19
- 3x + 19
3x + 19

5(x + 3) - 4(2x - 1) = 5x + 15 - 8x + 4 = -3x + 19

s

Question

Asked 5/9/2012 6:03:37 PM

Updated 1/10/2018 8:24:24 PM

1 Answer/Comment

Edited by Masamune [1/10/2018 8:24:23 PM]

Rating

3

5(x + 3) - 4(2x - 1)

= 5x + 15 - 8x + 4

= -3x + 19

= 5x + 15 - 8x + 4

= -3x + 19

Added 1/10/2018 8:24:24 PM

This answer has been confirmed as correct and helpful.

How much money is 15% of $20? **Weegy:** 15* of 20 is 3 **User:** Translate the phrase "three times some number is nine" into a Math statement **User:** Solve the Inequality: x - 1 **Weegy:** C.) X **User:** Solve the Inequality: x - 1 9
x > 11
x **User:** Find the value of the expression "6y + 1" when y = 3 **Weegy:** y=2 **User:** Subtract: (-5) - 11 **User:** Solve for x: 3x - 2 = 2x - 1 **Weegy:** Answer is X=1;
solution:
3x - 2 = 2x - 1 ;
3x-2x=-1+2;
x=1 (More)

Question

Expert Answered

Updated 7/30/2014 7:28:11 PM

4 Answers/Comments

Three times some number is nine" translate into a Math statement is X*3=9.

Assuming that the number is X. X*3=9. x=9/3,x=3.

Assuming that the number is X. X*3=9. x=9/3,x=3.

Added 7/30/2014 7:24:43 PM

The answer for the Inequality: x - 1 < 10 is x<11.

x - 1 < 10

x<10+1

x<11.

x - 1 < 10

x<10+1

x<11.

Added 7/30/2014 7:25:54 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/30/2014 7:35:35 PM], Rated good by andrewpallarca

Solve for x: 6x + 3 = 27 User: Find the value of the expression "6y + 1" when y = 3 **Weegy:** y=2 **User:** Translate the phrase "three times some number is nine" into a Math statement. (Points : 5)
3 + x = 9
3x + 9
3x = 9
None of these
**Weegy:** 9x^4. If you are satisfied with my answer, please click 'Good' on the ratings. Thank you! **User:** Translate the phrase "three times some number is nine" into a Math statement. (Points : 5)
A 3 + x = 9
B 3x + 9
C 3x = 9
D None of these **Weegy:** 3x = 18; 3x/3 = 18/3; x=6 **User:** Solve the Inequality: x - 1 9
x > 11
x **User:** Solve for x: 6x + 3 = 27 (Points : 5)
- 4
5
4
18
**Weegy:** x = -2 **User:** Find the value of the expression "6y + 1" when y = 3. (Points : 5)
18
19
10
21
**Weegy:** y=2 **User:** Using the correct Order of Operations, simplify as much as possible: **User:** Divide: (-6)/3 **Weegy:** 3^-6 = 0.0013717421. **User:** Subtract: (-5) - 11 **User:** add 4/3+1/3 (More)

Question

Updated 10/13/2014 8:17:28 AM

10 Answers/Comments

when y = 3, 6y + 1 = 6(3) + 1 = 18 + 1 = 19

Added 10/13/2014 8:14:17 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/15/2014 11:13:16 AM]

"three times some number is nine" into a Math statement is 3x = 9

Added 10/13/2014 8:15:01 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/15/2014 11:13:28 AM]

x - 1 < 10

x < 10 + 1

x < 11

x < 10 + 1

x < 11

Added 10/13/2014 8:15:39 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/15/2014 11:13:44 AM]

(-5) - 11 = -5 - 11 = -16

Added 10/13/2014 8:16:33 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/15/2014 11:13:47 AM]

31,918,943

questions answered

There are no comments.